Learning to feel at home in the Anthropocene: From state of emergency to everyday experiments in California's historic drought. (30th July 2018) - VINE, MICHAEL
ABSTRACT: In the deserts of Southern California, a series of climate crises has disturbed the form and content of the ordinary. In this context of unfolding change, Californians are experimenting with the spaces, surfaces, objects, and infrastructures of their homes, harnessing the material elements of the house as a site not only of repetition and reproduction but also of reinvention. At times, these experiments in the ecologies of everyday life unleash a range of transformative effects on both self and world, accreting into instances of cosmological reconfiguration. Rather than analyze such experiments as practices of adaptation or recovery, we can better understand them as attempts to cultivate alternative ways of feeling at home in the Anthropocene. Such experiments take up the relations among aesthetics, ethics, and affect as their primary site of improvisation and innovation.